L’IMPACT DES PESTICIDES SUR LA REPRODUCTION ET LES PARAMETRES PHYSIOLOGIQUES CHEZ LE LAPIN - Rebahi Samia (My University, 2025)
The objective of this study was to conduct an in-depth analysis of the deleterious effects of the herbicide Clodinafop Propargyl on reproduction, particularly on testicular function and structure. The study also aimed to evaluate its negative effects on certain physiological parameters in rabbits, such as body mass, as well as the weight and morphometry of target organs of toxicity (liver, kidneys, spleen, and testes), in addition to hematological parameters (complete blood count, CBC). To achieve this objective, a sample of twenty-four adult male domestic rabbits (Oryctolagus cuniculus), aged 5–6 months, was subjected to a medium-term experimental protocol. The animals were randomly divided into four groups, each consisting of six rabbits. Three experimental groups, labeled G1, G2, and G3, received increasing doses of Clodinafop Propargyl (1, 4, and 20 mg/kg/day, respectively) for a period of four weeks, while the fourth group served as the control. Body weight was measured daily. Hematological and hormonal analyses were performed, along with the assessment of morphometric characteristics such as weight, length, width, and thickness of the testes, liver, kidneys, and spleen. A sperm analysis was conducted to evaluate testicular function. In addition, histological examinations of testicular and epididymal samples were carried out to detect potential histological alterations. The results revealed a change in feeding behavior starting from the second week of herbicide administration, leading to a reduction in body weight gain and average daily gain (ADG) in treated rabbits compared with the control group. CBC analysis showed an increase in white blood cell count in groups treated with 1 mg/kg and 4 mg/kg of Clodinafop Propargyl, whereas a decrease in white blood cells was observed in the group receiving the highest dose (20 mg/kg). Furthermore, a reduction in red blood cells (RBCs), hemoglobin, platelets, and hematocrit was observed in the groups treated with 4 mg/kg and 20 mg/kg (Groups 2 and 3). A limited decrease was noted in Group 1 (1 mg/kg), while more pronounced effects were observed in Group 2. In addition, a significant decrease (P < 0.05) in testicular weight and morphometric measurements was recorded following herbicide administration, particularly in Group 3. In contrast, an increase in the weight and morphometric parameters of the liver, kidneys, and spleen was observed. A harmful effect on the hypothalamic–pituitary axis was also noted, resulting in a significant decrease in serum sexual hormone levels (testosterone),
يهدف هذا العمل هو تحليل الآثار الضارة لمبيد الاعشاب Clodinafop Propargylعلى التكاثر بشكل عميق، كما تهدف الدراسة إلى تقييم التأثيرات السلبية على بعض المعايير الفسيولوجية للأرانب، مثل وزن الجسم، وزن وأبعاد الأعضاء المستهدفـــة للتسمم (الكبد، الكلى، الطحال، الخصيتين)، وكذلك على المعايير البيولوجية للدم (FNS) لتحقيق هذا الهدف، تم تعريض عينة من أربعة وعشرين أرنبًا من الذكور البالغة (Oryctolagus cuniculus) والتي تتراوح أعمارها بين 5 إلى 6 أشهر لبروتوكول تجريبي متوسط المدى . تم تقسيم الأرانب عشوائيًا إلى أربع مجموعات، كل مجموعة تضم ستة حيوانات. تلقت ثلاث مجموعات تجريبية، تم تصنيفها كـ G1 وG2 وG3، لجرعات متزايدة من Clodinafop Propargyl(1 مجم/كجم/يوم، 4 مجم/كجم/يوم، و20 مجم/كجم/يوم على التوالي) لمدة أربعة أسابيع، أما الرابعة G4 فكانت مجموعة الشاهد. تم قياس الوزن الجسماني يوميًا، وتم إجراء تحاليل هيماتولوجية وهرمونية، وكذلك تقييم الخصائص المورفومترية مثل الوزن والطول والعرض والسمك للخصيتين والكبد والكلى والطحال. تم إجراء فحص للحيوانات المنوية لتقييم وظيفة الخصيتين، كما تم إجراء دراسة نسيجية لعينات من الخصيتين والبربخ للكشف على أي تغييرات نسيجية محتملة.أظهرت النتائج تغييرًا في سلوك التغذية بدءًا من الأسبوع الثاني من إعطاء المبيد الحشري، مما أدى إلى انخفاض في الزيادة اليومية المتوسطة (GMQ) لدى الأرانب المعالجة مقارنة بالمجموعة الشاهد.كشفت تحاليل FNS عن زيادة في عدد خلايا الدم البيضاء في المجموعة الأولى المعاملة بجرعة 1 مجم/كجم من Clodinafop Propargylبالمقابل لوحظ انخفاض في عدد خلايا الدم البيضاء في المجموعة التي تلقت أعلى جرعة وهي 20 مجم/كجم. علاوة على ذلك، تم ملاحظة انخفاض في عدد خلايا الدم الحمراء، والهيموغلوبين، والصفائح الدموية، والهيماتوكريت في المجموعات الثانية والثالثة المعالجة بجرعات 4 مجم/كجم و 20 مجم/كجم.تم تسجيل تأثير محدود على المجموعة 1، لكن لوحظت تأثيرات نسبية في المجموعة 2. بالإضافة إلى ذلك، تم تسجيل انخفاض كبير (P < 0.05) في القياسات المورفومترية للخصيتين والأوزان بعد إعطاء المبيد الحشري، خصوصًا في المجموعة 3. كذلك تم ملاحظة زيادة في وزن وقياسات الكبد و الكلي و الطحال المورفومترية.تم ملاحظة تأثير ضار على المحور تحت السرير العصبي - النخامي، مما أدى إلى انخفاض كبير في تركيزات الهرمونات الجنسية (التستوستيرون) في الدم، خاصة في المجموعة 3. أدت هذه الاختلالات الهرمونية إلى انخفاض في مؤشرات الحيوانات المنوية البيولوجية مثل التركيز، والحركة، والحيوية، حيث أظهرت زيادة في نسبة الحيوانات المنوية الميتة وانخفاض في نسبة الحيوانات المنوية الحية في المجموعات المعالجة بClodinafop Propargyl، خاصة في أعلى الجرعة، مقارنة بالمجموعة الضابطة، كما هو موضح في فحص الحيوانات المنوية ،علاوة على ذلك، تم تسجيل تغييرات هامة في النسيج المختبري للخصيتين لدى الأرانب التي خضعت للمعاملة مقارنة بالمجموعة الشاهدة. كانت التغييرات التي لوحظت تتمثل في التنكس في الأنابيب المنوية، كما يظهر من خلال وجود ضمور وتشوه، وظهور الظهارة غير المنتظمة وتقليل في الخلايا الجرثومية. حيث كانت هذه التغيرات ملحوظة بشكل خاص والتي تتمثل في انخفاض عدد الحيوانات المنوية عند الجرعات العالية (G3). يظهر المركب التجريبي Clodinafop Propargylتأثيرًا سلبيًا على المعايير الفسيولوجية للأرانب المعاملة، كذلك هناك تأثير سام تجاه الخصيتين لدى الأرانب الذكور المحلية، مما يؤدي إلى انخفاض كبير في الخصوبة بسبب الأضرار الهيكلية والوظيفية العميقة. الكلمات الدالة: Clodinafop Propargyl، التسمم، التستوستيرون، الأرنب، التكاثر، فحص الحيوانات المنوية، علم الانسجة.